Middleware model for adapting dynamic requirements - Suganthi, S.; Nadarajan, R. (Journal of Digital Information Management, 2012)
Making a distributed system adaptable to the dynamic variations in the user requirements is a big challenge in software industries. It is identified that the solution for the adaptability of such dynamic variations can be achieved through reflective middleware. In this paper an efficient solution is proposed by combining aspect oriented approach with reflective middleware. The significant feature of the proposed aspect oriented reflective middleware model is capturing the dynamic variations in the functionalities of the system as aspects. The three major components defined in this model to implement dynamic adaptability are Aspect Generator, Aspect Weaver and Remote Method Invoker. Aspect Generator component is used to define dynamic requirements as aspects. Aspect Weaver provides service to weave the dynamic requirements with the application components associated with that requirement. Remote Method Invoker is the meta layer component, which provides the platform for the Aspect Weaver to execute its service. The metric to measure the efficiency of the system adaptability has also been proposed here. The adaptability approach implemented through this model has been evaluated and proved as an efficient solution using this metric. This model has also been evaluated at an architectural level using formal analysis to prove that the dynamic requirements can be incorporated without affecting the existing functionalities of the system.
Keywords: Adaptability Metric; Aspect-Oriented Approach; Aspect-Oriented Reflective Middleware; Dynamic Adaptation; Dynamic Requirements; Reflective Middleware

Cache Pre-fetching and Replacement strategies for location dependent data in mobile environments - Mary Magdalene Jane, F.; Ilayaraja, N.; Nadarajan, R. (Journal of Digital Information Management, 2009)
In this paper, new strategies for prefetching and cache replacement are proposed. The proposed pre-fetching algorithm considers the geographical and semantic adjacency between queried items. The strategy is to pre-fetch the most probable secondary service as a by-product of the execution of a query to a primary service. Association rule mining is used for determining the secondary item that should be pre-fetched. The latter part of the paper deals with a cache replacement algorithm PAID+ (Probability Area Inverse Distance +) which takes into account the access probability and distance between the mobile client and the service item which suits a pre-fetching environment. The experimental evaluations using synthetic datasets show the cache pre-fetch and replacement policy PAID+ are effective in improving the system performance in terms of the cache hit ratio of mobile clients.
Keywords: Cache replacement; Location dependent data; Prefetching algorithm

Restricted continuous KNN queries on road networks with caching enhancement - Safar, M.; Ebrahimi, D.; Jane, M.M.F.; Nadarajan, R. (Journal of Digital Information Management, 2008)
Using a Global Positioning System (GPS) in the car navigation system enables the driver to perform a wide range of queries, from locating the car position, to finding a route from a source to a destination, or dynamically selecting the best route in real time. With spatial network databases (SNDB), objects are restricted to move on pre-defined paths (e.g., roads) that are specified by an underlying network. In our previous work, we proposed a novel approach, termed Progressive incremental Network Expansion (PINE), to efficiently Support several spatial queries. In this work, we utilize our developed PINE system to efficiently support Restricted Continuous K Nearest Neighbors (RCKNNs) queries. RCKNN continously finds the K nearest objects to a query point an a given path that are within a specified distance bound. Our solution addresses a new type of query that is plausible to many applications where the answer to the query not only depends an the distances of the nearest neighbors, but also on the user ar application needs. By distinguishing between two types of split points, we reduce the number of computations required to retreive the RCKNNs of moving object. We futher define a caching model to expedite RCKNN query response time.
Keywords: Navigation system; Network databases; Spatial databases